2009
DOI: 10.1369/jhc.2009.954206
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Stem Cell Transplantation Correlates With Endogenous Neurogenin 3 Expression and Pancreas Regeneration in Streptozotocin-injured Mice

Abstract: S U M M A R Y Pancreatic b cell regeneration remains poorly understood, yet stimulation of adult b cell neogenesis could lead to therapies for type 1 and type 2 diabetes. We studied the effect of embryonic stem (ES) cell transplantation on pancreas regeneration following b cell injury. Female Balb/c nude mice were treated with streptozotocin to induce hyperglycemia and received an ES cell transplant 24 hr later beneath the renal capsule. Transplantation of ES cells prevented hyperglycemia in a subset of mice, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In STZ-treated hyperglycemic mice, Neurog3 expression is upregulated; nevertheless, the same authors reported different Neurog3 expression patterns (i.e. in islets or in ducts) in different papers [38,39]. In another work, the induced regeneration after 60% PX in mice did not appear to involve Neurog3 re-expression [40].…”
Section: Reviewmentioning
confidence: 99%
“…In STZ-treated hyperglycemic mice, Neurog3 expression is upregulated; nevertheless, the same authors reported different Neurog3 expression patterns (i.e. in islets or in ducts) in different papers [38,39]. In another work, the induced regeneration after 60% PX in mice did not appear to involve Neurog3 re-expression [40].…”
Section: Reviewmentioning
confidence: 99%
“…These multi-hormonal endocrine cells, a characteristic of beta cell regeneration, suggested possible divergence from embryonic islet cell development (Kodama et al, 2008). In another study, Kodama et al (2009) showed that transplanted ESCs could migrate into the injured pancreas. Cell tracing analysis showed that significant beta cell neogenesis occurred 2 to 3 weeks after injury.…”
Section: Stem Cell Transplantationmentioning
confidence: 97%
“…Importantly, whereas pancreas-localised ESC or their derivatives were found adjacent to the sites of regeneration, neogenic pancreatic epithelia, including Ngn3+ cells, were endogenous. Transplantation efficiency was confirmed by enhanced endogenous regeneration and increased beta cell differentiation from endogenous progenitor cells (Kodama et al, 2009). …”
Section: Stem Cell Transplantationmentioning
confidence: 97%
See 1 more Smart Citation
“…Nowadays, fluorescence in situ hybridization (FISH) plays a significant role in many research algorithms and became indispensable for routine clinical cytogenetic diagnostics (Tkachuk et al 1991; Ried et al 1992; Bednarz et al 2010; Anguiano et al 2012; Wallander et al 2012). For example, in prenatal/pre-implantation genetic analyses (Cassel et al 1997; Bucksch et al 2012) or stem cell research (Hessel et al 1996; Weier et al 2004; Kwon et al 2010), as a means of controlling the rate of fetal cellular proliferation at the fetal-maternal interface (Weier et al 2005; Weier et al 2010) or determining the fate of regenerating tissues, assessment of aneuploidy may be of substantial importance (Pujol et al 2003; Kodama et al 2009; Kwon et al 2010). However, whereas other methods, such as chorionic villus sampling (CVS) with in vitro culture-based karyotyping of metaphase spreads, have presented difficulties in detecting aneusomies because abnormal cells can arise in any portion of the placenta or fetal-maternal interphase but might not be proliferating (Weier et al 2005), we rely on chromosome-specific FISH assay to accurately determine the cellular chromosome complements in interphase cells.…”
mentioning
confidence: 99%